КОНТРАСТИВ, КОНФРОНТАТИВ ВА ЧОҒИШТИРМА ТИЛШУНОСЛИК АТАМАЛАРИ ХУСУСИДА (Scientific journal of the Fergana State University, 2023)
The article considers the issue of enlightenment of the notions of contrastive linguistics, confrontative linguistics, comparative linguistics in World linguistics.